2008
DOI: 10.1007/s11912-008-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of relapsed diffuse large B-cell lymphoma

Abstract: Despite more effective front-line regimens, a substantial portion of patients with diffuse large B-cell lymphoma relapse and require further therapy. Several trials have established the efficacy of autologous stem cell transplantation for relapsed diffuse large B-cell lymphomas, but the benefit has been largely restricted to patients with chemosensitive disease and low-risk features at the time of relapse. In an effort to improve outcomes following an autologous transplant, researchers are exploring several av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…1 Even though there have been substantial advances in treatment options for these cancers, including chemotherapy, either with or without monoclonal antibodies, >22,000 patients succumb to their disease yearly. [1][2][3][4] Clearly, there is a need for new therapeutic options for patients who are failed by the frontline therapies for these B-cell malignancies. One promising treatment option involves the adoptive transfer of T cells that target molecules on the surface of B-cell cancers.…”
Section: Introduction the Incidence Of B-cell Malignancies Continuesmentioning
confidence: 99%
“…1 Even though there have been substantial advances in treatment options for these cancers, including chemotherapy, either with or without monoclonal antibodies, >22,000 patients succumb to their disease yearly. [1][2][3][4] Clearly, there is a need for new therapeutic options for patients who are failed by the frontline therapies for these B-cell malignancies. One promising treatment option involves the adoptive transfer of T cells that target molecules on the surface of B-cell cancers.…”
Section: Introduction the Incidence Of B-cell Malignancies Continuesmentioning
confidence: 99%
“…Interestingly, multivariate analysis revealed that prior anti-CD20 therapy did not affect the incidence of disease progression or relapse following the transplant. Allogeneic SCT is associated with a graft-versus-lymphoma effect that could reduce the chances of post-transplantation relapse [88], but the final outcome is heavily dependent upon tumour histology [106]. Thus, the question of optimal patient selection based on disease characteristics is a major barrier to establishing the efficacy of allogeneic SCT and the appropriate conditioning regimens.…”
Section: Treatment Of Relapsed Diseasementioning
confidence: 99%
“…The ideal preparative regimen should be capable of targeting residual malignant cells with minimal impact to healthy organ systems. [14] Although the choice of conditioning regimen varies and is typically based on institutional experience, BEAM is the preferred option for the treatment of NHL and HL. [15,16] The cyclophosphamide, carmustine, etoposide (CBV) regimen is also commonly used in North America.…”
Section: Introductionmentioning
confidence: 99%